A new spray‐based method for the in‐vitro development of dry‐surface biofilms. Issue 1 (11th January 2023) - Christine, Esther; Olive, Claude; Louisin, Myriam; Dramé, Moustapha; Marion‐Sanchez, Karine
Abstract: The inanimate environment immediately surrounding the patient in healthcare facilities is a reservoir of microorganisms embedded in dry‐surface biofilms (DSB). These biofilms, first highlighted in 2012, are increasingly studied, but currently available in‐vitro models only allow for the growth of semi‐hydrated biofilms. We developed a new in‐vitro method under actual dehydration conditions based on the hypothesis that surface contamination is mainly due to splashes of respiratory secretions. The main objective of this study was to show that the operating conditions we have defined allowed the growth of DSB with a methicillin resistant Staphylococcus aureus strain. The second objective was to show that extended‐spectrum beta‐lactamase‐producing Enterobacteriaceae, that is, Klebsiella pneumoniae and Enterobacter cloacae were also able to grow such biofilms under these conditions. Monobacterial suspensions in sterile artificial saliva (SAS) were sprayed onto polyethylene surfaces. Nutrients and hydration were provided daily by spraying SAS enriched with 20% of Brain Heart Infusion broth. The primary outcome was mean surface coverage measured by image analysis after crystal violet staining. The method applied to S. aureus for 12 days resulted in reproducible and repeatable DSB consisting of isolated and confluent microcolonies embedded in extracellular polymeric substances as shown in scanning electron microscopy images. Similar DSB were obtained with both Enterobacteriaceae applying the same method. No interspecies variation was shown between the three strains in terms of surface coverage. These first trials are the starting point for a 3‐year study currently in process. Abstract : Bacteria can persist in the hospital environment inside dry biofilms which grow on inanimate surfaces surrounding the patients. We developed a new method to produce dry‐surface biofilms using the spraying of enriched artificial saliva which mimics the dispersion of respiratory secretions. The method created dehydrated biofilms of methicillin resistant Staphylococcus aureus and Enterobacteria under real‐world conditions.